Identification of a dietary pattern associated with lower high molecular weight adiponectin in breast cancer survivors - Mohd Razif, Shahril; Nor Syamimi, Zakarai; Geeta, Appannah; Aryati, Ahmad; Hamid JanJan, Mohamed (2019)
Background/Aims: Energy dense, high saturated fat, low fibre diets may contribute to obesity in breast cancer survivors, how-ever their relationships with high molecular weight (HMW) adi-ponectin are unclear. We examined associations between an 'en-ergy-dense, high saturated fat and low-fibre' dietary pattern (DP) and HMW adiponectin in breast cancer survivors. Methods: Data was obtained from 96 participants in the East Coast of Peninsular Malaysia Breast Cancer Survivors Study. Dietary intake, anthropo-metric and 1-IMW adiponectin were measured and z-scores for an 'energy dense, high saturated fat and low fibre' DP were estimated using reduced rank regression (RRR). Associations between DP z-scores and IIMW adiponectin were examined using regression models. Results: The results of this study show that, a 1 unit in-crease in DP z-score was associated with a 0.41 Rg/mL lower HMW adiponectin (95% CI: —0.806, —0.014) independently of age, BMI, cancer stage, duration since diagnosis, education level and occupa-tion status. The 'energy dense, high saturated fat and low fibre' DP which was characterized by high intake of sugar sweetened bever-ages and fat-based spread while lower intake of fruits and vegeta-bles were further examined to find which food groups contributed significantly to the association. Interestingly no significant find-ings were found supporting that totality of the diet provides more accurate description of actual dietary exposure. Conclusion: As a conclusion, 'energy dense, high saturated fat, low fibre' DP is neg-atively associated with HMiA, adiponectin. This finding could serve as a basis in examining the relationship between dietary ex-posure, obesity and cancer survivorship.